Slow wave activity and slow oscillations in sleepwalkers and controls: effects of 38 h of sleep deprivation. (11th February 2013) - Perrault, Rosemarie; Carrier, Julie; Desautels, Alex; Montplaisir, Jacques; Zadra, Antonio
Summary Sleepwalkers have been shown to have an unusually high number of arousals from slow wave sleep and lower slow wave activity (SWA) power during the night than controls. Because sleep deprivation increases the frequency of slow wave sleep (SWS) arousals in sleepwalkers, it may also affect the expression of the homeostatic process to a greater extent than shown previously. We thus investigated SWA power as well as slow wave oscillation (SWO) density in 10 sleepwalkers and nine controls at baseline and following 38 h of sleep deprivation. There was a significant increase in SWA during participants' recovery sleep, especially during their second non‐rapid eye movement (NREM) period. SWO density was similarly increased during recovery sleep's first two NREM periods. A fronto‐central gradient in SWA and SWO was also present on both nights. However, no group differences were noted on any of the 2 nights on SWA or SWO. This unexpected result may be related to the heterogeneity of sleepwalkers as a population, as well as our small sample size. SWA pressure after extended sleep deprivation may also result in a ceiling effect in both sleepwalkers and controls.